2015
DOI: 10.18257/raccefyn.143
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma rangeli: un protozoo infectivo y no patógeno para el humano que contribuye al entendimiento de la transmisión vectorial y la infección por Trypanosoma cruzi, agente causal de la enfermedad de Chagas

Abstract: T. rangeli: modelo para la transmisión vectorial e infección por T. cruzi111 Rev. Acad. Colomb. Cienc. Ex. Fis. Nat. 39(150):111-122, enero-marzo de 2015 Trypanosoma rangeli: un protozoo infectivo y no patógeno para el humano que contribuye al entendimiento de la transmisión vectorial y la infección por Trypanosoma cruzi, agente causal de la enfermedad de Chagas Gustavo ResumenA diferencia de Trypanosoma cruzi, agente causal de la enfermedad de Chagas, Trypanosoma rangeli es un parásito infectivo y no patóg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 47 publications
3
20
0
12
Order By: Relevance
“…It is interesting to note that T. rangeli stocks from Rhodnius spp. (Pallescens lineage) were identified in the KP1(-) group and lineage C, an association that has been proposed (Vallejo et al 2015). However, the reference strain R1625 (human origin) was classified in the lineage C (Maia-da-Silva et al 2007), although being KP1(+), as reported by Sincero et al (2015) and confirmed by our results.…”
Section: Biochemical and Molecular Analysessupporting
confidence: 89%
See 3 more Smart Citations
“…It is interesting to note that T. rangeli stocks from Rhodnius spp. (Pallescens lineage) were identified in the KP1(-) group and lineage C, an association that has been proposed (Vallejo et al 2015). However, the reference strain R1625 (human origin) was classified in the lineage C (Maia-da-Silva et al 2007), although being KP1(+), as reported by Sincero et al (2015) and confirmed by our results.…”
Section: Biochemical and Molecular Analysessupporting
confidence: 89%
“…As far we know, KP1(+) and KP1(-) T. rangeli strains have not yet been compared by their morphological and biological features, and the present paper evidenced other peculiarities of the SC-58 and SC-61 isolates from P. dasythrix from Santa Catarina Island. Recent molecular studies (Sincero et al 2015) point to a subdivision within the KP1(-) group, which corroborate the uniqueness of these isolates, besides others from wild Panstrongylus megistus from the same region (Vallejo et al 2002(Vallejo et al , 2015. This may reflect a process of speciation within T. rangeli, as advanced by some authors (Macedo et al 1993, closely associated to the vector lineages (Machado et al 2001;Vallejo et al 2002Vallejo et al , 2015Urrea et al 2005Urrea et al , 2011Maia-da-Silva et al 2007;Salazar-Antón et al 2009;Barreto-Santana et al 2015;Sincero et al 2015).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…It is recognized that the species of triatominae belonging to the genus Rhodnius are susceptible to infection by Trypanosoma rangeli, and the occurrence has already been recorded in the following species: Rhodnius domesticus, Rhodnius nasutus, Rhodnius neglectus 4 8 .…”
mentioning
confidence: 99%